Endolymphatic Sac Enlargement in a Girl with a Novel Mutation for Distal Renal Tubular Acidosis and Severe Deafness - Rink Nikki; Bitzan Martin; O'Gorman Gus; Nagel Mato; Torban Elena; Goodyer Paul (Hindawi Limited, 2012)
Hereditary distal renal tubular acidosis (dRTA) is caused by mutations of genes encoding subunits of the H+-ATPase (ATP6V0A4 and ATP6V1B1) expressed in α-intercalated cells of the distal renal tubule and in the cochlea. We report on a 2-year-old girl with distal RTA and profound speech delay which was initially misdiagnosed as autism. Genetic analysis showed compound heterozygous mutations with one known and one novel mutation of the ATP6V1B1 gene; cerebral magnetic resonance imaging (MRI) revealed bilateral enlargement of the endolymphatic sacs of the inner ear. With improved cooperation, audiometric testing showed that hearing loss was most profound on the right, where endolymphatic sac enlargement was greatest, demonstrating a clear link between the degree of deafness and the degree of inner ear abnormality. This case indicates the value of MRI for diagnosis of inner ear involvement in very young children with distal RTA. Although citrate therapy quickly corrects the acidosis and restores growth, early diagnosis of deafness is crucial so that hearing aids can be used to assist acquisition of speech and to provide enough auditory nerve stimulation to assure the affected infants remain candidates for cochlear implantation.